Microstructural Development of Fe-Cr-C and B4C Powder Alloy Coating on Stainless Steel by Plasma-Transferred Arc Weld Surfacing - Buytoz, Soner; Orhan, Ayhan; Gur, Ali Kaya; Caligulu, Ugur (Springer Heidelberg, 2013)
The present investigation discusses the effects of B4C addition on the morphologies of primary carbides and eutectic colonies in Fe-Cr-C weld-surfacing alloys. Results reveal that a series of Fe-Cr-C weld-surfacing alloys with different B4C contents are successfully fabricated onto AISI 316 stainless steel by plasma-transferred arc welding. The microstructure of the coatings is mainly gamma-Fe,Ni eutectic matrix, and hexagonal M(=Cr, Fe)(7)(C,B)(3) and M(=Cr, Fe)(23)(C,B)(6) carbides are non-uniformly distributed in the eutectic matrix. The average microhardness of the cladding coating is 820HV, which is almost five times of that of the AISI 316 stainless steel substrate (180HV). The maximum microhardness value of the coating is about 1,280HV. Higher current levels have resulted in higher dilution levels and also in melting/burning of the substrate.
Keywords: Plasma-transferred arc coating; Fe-Cr-C alloys; Bor carbide; Microstructure